THE FEATURES OF PROCESSES OF SKILLS (SPECIAL COMPETENCIES) FORMATION - A. N. Pechnikov; A. V. Prenzov; A. A. Mashoshina (Образование и наука)
Introduction. The present article continues a series of the authors’ publications devoted to key problems of a modern educational process organization and ensuring its efficiency. A starting point of the latest investigation stage has been a gap between the available models of formation and diagnostics of special competencies and the tasks for predicting a degree of success of development student’s skills in order to take adequate decisions on managing the process.The aim of the article is justification of a new methodological approach to formation of skills (special competencies) of students.Methodology and research methods. The methods of analysis and synthesis; fundamental principles of didactics, qualimetry, the efficiency theory and the decision-making theory were used.Results and scientific novelty. The theoretical bases of evaluation procedures of pupils’ skills created during training are stated. Reference points for the choice of learning process characteristics are designated; by following those characteristics it is possible to provide better development of skills. The tasks of analysis of the studied problem, information acquisition and modeling of the “situation mechanism” of special competencies formation are considered. It is proved that for educational process management optimization it is necessary to evaluate not only its result, but also its quality process, as well its quality system that provides the organization process. The combination of factors to exert the dominating influence over educational process effectiveness are singled out: a type of the applied pedagogical influence; a type of the realized didactic system; a set of personal trainee characteristics which include levels of his/her educational motivation, learning ability, creativity and enables to model and predict training results. It is shown that each of possible combinations of the leading factors represents separate version of a solution to the problem of the students’ skills formation process. The conclusion is drawn that these particular options have to make an initial set of alternatives for the educational process organization.Practical significance. This work has revealed basic features of variable processes for formation of skills (special competencies) of students to create correct, exact and reliable tools for measurement of learning outcomes.